Supply chain risk management: An exploratory research in Brazilian aerospace industry - Funo, Kelly Ayumi [UNESP]; Muniz, Jorge [UNESP]; Silva Marins, Fernando Augusto [UNESP]; Salomon, Valerio A.P. [UNESP] (Inderscience Publishers, 2011)
This paper aimed to analyse supply chain risk factors in aerospace industry. It was conducted an exploratory research at an important Brazilian aerospace company. This company has a major role at the global aerospace industry. Senior managers assessed risk factors such as quality, productivity, supply chain, business strategy, organisation, environmental and natural political, indicators, product management, and information system. Analytic hierarchy process was applied to prioritise these factors. The most relevant were quality and productivity. Copyright © 2011 Inderscience Enterprises Ltd.
Keywords: Aerospace industry; AHP; Analytic hierarchy process; Brazil; Risk management; Supply chain management